A Digital Approach for a Complete Rehabilitation with Fixed and Removable Prostheses: A Technical Procedure - Etienne Lefrançois; Victor Delanoue; Samuel Morice; Xavier Ravalec; Marie Desclos-Theveniau (Dentistry Journal)
Background: The present article describes a step-by-step maximally digitalized workflow protocol with computer-aided design and computer-aided manufacturing (CAD/CAM) in partial-arch edentulous patients rehabilitated with fixed dental prostheses and removable partial dentures (FDPs and RPDs). Methods: Facial digitalization, intraoral scans, and functional mandibular movement recordings were used to create a 4D virtual patient on commercially available CAD software. The fixed components including post-and-cores, both metal–ceramic with extra-coronal attachment and monolithic zirconia crowns, and the RPDs were manufactured by computer numerical controlled direct milling. Results: This innovative digital approach using the virtual patient and the superimposition of interim RPDs fitted in the mouth has been used to provide fixed and removable rehabilitation to the patient without clinical complications with 2 years of follow-up. Conclusions: Within the limitations of this report, the developed combined prosthesis fabrication technique allowed optimization of the production by decreasing the clinical steps and laboratory procedures in partial-arch edentulous rehabilitated with FDPs and RPDs.